Prenatal food restriction induces poor-quality articular cartilage in female rat offspring fed a post-weaning high-fat diet and its intra-uterine programming mechanisms. Issue 8 (29th September 2016) - Tan, Yang; Wu, Yunpeng; Ni, Qubo; Deng, Yu; Li, Jing; Wang, Linlong; Shen, Lang; Liu, Yansong; Magdalou, Jacques; Wang, Hui; Chen, Liaobin
Abstract: Epidemiological data show that osteoarthritis (OA) is significantly associated with lower birth weight, and that OA may be a type of fetal-originated adult disease. The present study aimed to investigate the prenatal food-restriction (PFR) effect on the quality of articular cartilage in female offspring to explore the underlying mechanisms of fetal-originated OA. Maternal rats were fed a restricted diet from gestational day (GD) 11 to 20 to induce intra-uterine growth retardation. Female fetuses and female adult offspring fed a post-weaning high-fat diet were killed at GD20 and postnatal week 24, respectively. Serum and knee cartilage samples from fetuses and adult female offspring were collected and examined for cholesterol metabolism and histology. Fetal serum corticosterone and insulin-like growth factor-1 (IGF-1) in the PFR group were lower than those of the control, but the serum cholesterol level was not changed. The lower expression of IGF-1 in the PFR group lasted into adulthood. The expression of extracellular matrix (ECM) genes, including type II collagen, aggrecan and cholesterol efflux genes including liver X receptor, were significantly induced, but the ATP-binding-cassette transporter A1 was unchanged. PFR could induce a reduction in ECM synthesis and impaired cholesterol efflux in female offspring, and eventually led to poor quality of articular cartilage and OA.